THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL INCLUSION ON MSME PERFORMANCE WITH FINANCIAL MANAGEMENT BEHAVIOR AS AN INTERVENING VARIABLE IN MSMES IN WEST JAVA PROVINCE - Gyska Restiana, Nanda; Silviana (JURNAL SIGNAL, 2025)
The number of MSME units in 2023 has increased, but the fact is that from this increase, MSME actors are less able to maintain their performance which has an impact on reducing their productivity, conceptually if the unit increases, the amount of production increases, but the gap phenomenon here is the lack of ability of MSME actors in managing their business, especially from the aspect of financial management. This study observes and analyzes using a descriptive quantitative approach which is defined as a tool to describe the situation and condition of their facts and symptoms obtained while the analytical tool used is using SEM using 400 SMEs in West Java. The results of the study state that financial literacy affects the performance of MSMEs, financial inclusion affects the performance of MSMEs, financial literacy affects the financial management behavior of MSME actors, financial inclusion has no effect on the financial management behavior of MSME actors, financial management behavior affects the performance of MSMEs, financial literacy affects the performance of MSMEs with financial management behavior as an intervening variable and financial inclusion affects the performance of MSMEs with financial management behavior as an intervening variable.